Macroanatomic investigations on arteria celiaca and its branches in malakan horse - İftar Gürbüz; Mustafa Orhun Dayan; Yasin Demiraslan; Kadir Aslan (Eurasian Journal of Veterinary Sciences)
Aim: In the study, it was aimed to investigate the branches of Materials and Methods: In the study, 5 male and 5 female adult Malakan horses were used. After opening the abdominal cavity of the horses, the colored latex, by entering from the aorta abdominalis, was injected to the vessel. Results: It was determined that arteria celiaca was divided into three rami as arteria hepatica, arteria gastrica sinistra and arteria lienalis. It was determined that diamater of the arteria hepatica were average of 7.36 mm in male and 7.00 mm in female, diamater of the arteria gastrica sinistra were average of 5.56 mm in male and 4.95 mm in female, the diamater of the arteria lienalis were average of 8.79 mm in male and 7.50 mm in female. Arteria hepatica gave the rami pancreatici, ramus hepaticus, arteria gastrica dextra and, continued the course as arteria gastroduodenalis. After arteria gastrica sinistra gave the rami pancreatici, it was divided into ramus parietalis and ramus visceralis. Ramus parietalis gave the ramus esophageus for the esophageal vascularization. It was determined that the arteria gastrica breves, rami pancreatici, rami splenici, rami epiploici emerged from arteria lienalis and, arteria lienalis coursed as arteria gastroepiploica sinistra. Conclusions: In conclusion, the findings were similar at high rates by literature.